Validity of the Fisher Community Knowledge-Based Economic Valuation of the Local Ecosystem for Oyster Farming: A Case Study in Japan - Shinji, Junpei; Kamiyama, Ryutaro; Nakamura, Tsubasa; Yamanaka, Kenshiro; Matsui, Takahiro (Frontiers in Marine Science, 2022)
The importance of local knowledge as a relevant information resource for ecosystem conditions has recently been the focus of sustainable ecosystem management. However, the accuracy of economic evaluation based on local knowledge regarding ecosystems has not yet been discussed, despite most activities in human society, including ecological conservation, being monetarily mediated. This study reports the correspondence between the economic value estimated by the fisher community and the analyzed environmental factors in the marine areas sectioned for oyster farming in Japan. At the study site, community-agreed usage fees for the area sections showed a gradient from the inner to the outer part of the bay. Our numerical modeling showed that the gradient of the economic value correlated with oyster feeding efficiency, indicating that a better location for feeding was empirically evaluated at a high price by the local fisher community. This suggests that the economic evaluation based on the local knowledge was biologically reasonable and could be a reliable information source for the aim of the area use in the study site.